Copolymerization of lactones and bioaromatics via concurrent ring-opening polymerization/polycondensation. Issue 8 (16th January 2017) - Nguyen, Ha Thi Hoang; Short, Gabriel N.; Qi, Pengxu; Miller, Stephen A.
Abstract : Concurrent ring-opening polymerization/polycondensation of lactones and bioaromatic hydroxy-acids yields random copolymers with improved and controlled thermal properties. Abstract : The general and efficient copolymerization of lactones with hydroxy-acid bioaromatics was accomplished via a concurrent ring-opening polymerization (ROP) and polycondensation methodology. Suitable lactones werel -lactide or ε-caprolactone and four hydroxy-acid comonomers were prepared as hydroxyethyl variants of the bioaromatics syringic acid, vanillic acid, ferulic acid, and p -coumaric acid. Copolymerization conditions were optimized on a paradigm system with a 20 : 80 feed ratio of caprolactone : hydroxyethylsyringic acid. Among six investigated catalysts, polymer yield was optimized with 1 mol% of Sb2 O3, affording eight copolymer series in good yields (32–95% for lactide; 80–95% for caprolactone). Half of the polymers were soluble in the GPC solvent hexafluoroisopropanol and analyzed to high molecular weight, with M n = 10 500–60 700 Da. Mass spectrometry and 1 H NMR analysis revealed an initial ring-opening formation of oligolactones, followed by polycondensation of these with the hydroxy-acid bioaromatic, followed by transesterification, yielding a random copolymer. By copolymerizing bioaromatics withl -lactide, the glass transition temperature ( T g ) of polylactic acid (PLA, 50 °C) could be improved and tuned in the range of 62–107 °C; the thermal stability ( T 95% ) of PLA (207 °C) could be substantially increased up to 323 °C. Similarly, bioaromatic incorporation into polycaprolactone (PCL, T g = −60 °C) accessed an improved T g range from −48 to 105 °C, while exchanging petroleum-based content with biobased content. Thus, this ROP/polycondensation methodology yields substantially or fully biobased polymers with thermal properties competitive with incumbent packaging thermoplastics such as polyethylene terephthalate ( T g = 67 °C) or polystyrene ( T g = 95 °C).